Inhaled Nitric Oxide at Birth Reduces Pulmonary Vascular Resistance and Improves Oxygenation in Preterm Lambs - Satyan Lakshminrusimha; Sylvia F. Gugino; Krishnamurthy Sekar; Stephen Wedgwood; Carmon Koenigsknecht; Jayasree Nair; Bobby Mathew (MDPI AG, 2021)
Resuscitation with 21% O2 may not achieve target oxygenation in preterm infants and in neonates with persistent pulmonary hypertension of the newborn (PPHN). Inhaled nitric oxide (iNO) at birth can reduce pulmonary vascular resistance (PVR) and improve PaO2. We studied the effect of iNO on oxygenation and changes in PVR in preterm lambs with and without PPHN during resuscitation and stabilization at birth. Preterm lambs with and without PPHN (induced by antenatal ductal ligation) were delivered at 134 d gestation (term is 147-150 d). Lambs without PPHN were ventilated with 21% O2, titrated O2 to maintain target oxygenation or 21% O2 + iNO (20 ppm) at birth for 30 min. Preterm lambs with PPHN were ventilated with 50% O2, titrated O2 or 50% O2 + iNO. Resuscitation with 21% O2 in preterm lambs and 50%O2 in PPHN lambs did not achieve target oxygenation. Inhaled NO significantly decreased PVR in all lambs and increased PaO2 in preterm lambs ventilated with 21% O2 similar to that achieved by titrated O2 (41 ± 9% at 30 min). Inhaled NO increased PaO2 to 45 ± 13, 45 ± 20 and 76 ± 11 mmHg with 50% O2, titrated O2 up to 100% and 50% O2 + iNO, respectively, in PPHN lambs. We concluded that iNO at birth reduces PVR and FiO2 required to achieve target PaO2.